Status and conservation of coral reefs in Costa Rica - Cortés, Jorge (Universidad de Costa Rica, 2010)
Costa Rica has coral communities and reefs on the Caribbean coast and on the Pacific along the coast and off-shore islands. The Southern section of the Caribbean coast has fringing and patch reefs, carbonate banks, and an incipient algal ridge. The Pacific coast has coral communities, reefs and isolated coral colonies. Coral reefs have been seriously impacted in the last 30 years, mainly by sediments (Caribbean coast and some Pacific reefs) and by El Niño warming events (both coasts). Monitoring is being carried out at three sites on each coast. Both coasts suffered significant reductions in live coral cover in the 1980’s, but coral cover is now increasing in most sites. The government of Costa Rica is aware of the importance of coral reefs and marine environments in general, and in recent years decrees have been implemented (or are in the process of approval) to protect them, but limited resources endanger their proper management and conservation, including proper outreach to reef users and the general public.